A descriptive study on the effect celebrity endorsements have on consumers' purchase intentions. - Moloabi, Masego (The IIE, 2022)
The following research aims to investigate the effects celebrity endorsements has on consumer purchase intention with respect to their source of credibility model from Ohanian (1990) in harmony on consumer’s attitude towards purchase intention and the brand. Celebrity endorsement has been popular as one of the techniques to market businesses’ products or services these days. This research assesses the efficiency of this communication marketing tool. Data has been collected by 30 respondents on an online questionnaire survey. A bit of descriptive analysis was used. The result showed that source of credibility model of celebrity endorsement has no longer have a significant affect on consumers.
Keywords: Customer behaviour; Celebrities; Influencers; Marketing